Present Stage of Chemotherapy and Chemoprophylaxis of Rickettsiosis and Q Fever - E. A. Yakovlev; E. P. Lukin; S. V. Boricevich (Антибиотики и Химиотерапия, 2020)
The analysis of the published experimental and clinical data on chemoprophylaxis and chemotherapy of rickettsiosis and Q fever confirmed the preserved role of doxycycline, the main drug of choice in the treatment of the diseases, then followed chloramphenicol. Macrolides, such as azithromycin and clarithromycin proved to be useful in pediatric practice and the treatment of pregnant women with rickettsiosis. The treatment of acute and chronic Q fever required the use of doxycycline, fluoroquinolobes, co-trimoxazole and hydroxachloroquine in combined therapy. It is concluded that in vivo studies of novel drugs and investigation of prospective macrolides and fluoroquinolones are necessary. Clinical trials of a new glycycline, i.e. tigecycline, which experimentally showed highy strong activity against the Q fever pathogen, should be accelerated.